Mira's diary : lost in Paris - Moss, Marissa (Moss, Marissa. Mira's diary., 2012)
Mira is shocked when she receives a postcard from her missing mother--from Paris! Her father decides it's time for a trip to France to search for her. While visiting Notre Dame, Mira touches a gargoyle and is whirled into the past. There she meets the famous painter Degas and catches a brief, shocking glimpse of her mother. Mira begins to suspect that her mom didn't run out on them but is a prisoner of the past. Can one family on an incredible worldwide adventure stop a plot in time?